2019
DOI: 10.1111/ipd.12471
|View full text |Cite
|
Sign up to set email alerts
|

How much does household food insecurity explain income inequalities in untreated dental caries?

Abstract: Background The pathway by which socioeconomic disadvantages are manifested in the occurrence of dental caries remains unclear. Aim To explore how much the association between untreated dental caries and income inequalities is related to household food insecurity (HFI). Design A population‐based study was conducted with a sample of 466 12‐year‐old students. Dental caries was evaluated by an examiner who had undergone calibration exercises. HFI was assessed using the Food Insecurity Scale validated for Brazilian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…Consistent with our main hypothesis, the finding from this nationally representative study of 5-17 year old children was that those living in food insecure households reported having significantly poorer oral health than their food secure counterparts. This finding is also consistent with prior studies reporting on similarly aged children from Brazil (10)(11)(12) and several high-income countries (13)(14)(15)(16)(17)(18)(19) despite differences in study designs, methods used to assess HFI and oral health, and data analysis. The study also provided insights about potential dietary and non-dietary mediators of the HFI-child oral health relationship.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with our main hypothesis, the finding from this nationally representative study of 5-17 year old children was that those living in food insecure households reported having significantly poorer oral health than their food secure counterparts. This finding is also consistent with prior studies reporting on similarly aged children from Brazil (10)(11)(12) and several high-income countries (13)(14)(15)(16)(17)(18)(19) despite differences in study designs, methods used to assess HFI and oral health, and data analysis. The study also provided insights about potential dietary and non-dietary mediators of the HFI-child oral health relationship.…”
Section: Discussionsupporting
confidence: 91%
“…However, the relationship of HFI with oral health is understudied in school-age children especially those from low-and-middle income countries (LMIC). Except for Brazil, (10)(11)(12) published studies are limited to three high-income countries, i.e., the U.S. (13)(14)(15)(16) , New Zealand (17)(18) and South Korea (19) . This is an important gap in knowledge since both the population burdens of HFI (20) and childhood oral disease are elevated in Latin American and other LMICs compared to high-income countries (5,21) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, 83.22% had a monthly income of more than PKR 15000. This population showed a lower frequency of caries which is consistent with international studies that highlight the relationship of high income with lower risk of dental caries 17,18 . Moreover, the education status played a great role in the development of dental caries, as educated families had better opportunities and had less prevalence of dental caries as was reported by our study in which more than half of the study population was educated and thus showed less prevalence 12 .…”
Section: Discussionsupporting
confidence: 90%